2003
DOI: 10.1590/s1415-47572003000200014
|View full text |Cite
|
Sign up to set email alerts
|

Localization of 45S rDNA and telomeric sites on holocentric chromosomes of Rhynchospora tenuis Link (Cyperaceae)

Abstract: Rhynchospora tenuis Link (Cyperaceae) is a weed widely distributed in Brazil that presents a small number of holocentric chromosomes (2n = 4) with some autopolyploid populations (2n = 8). The haploid number n = 2 is considered as a derivative of the base number x = 5. 45S rDNA probes and telomeric DNA were hybridized in both chromosome races of R. tenuis, looking for indications of chromosome fusions. The results showed that hybridization sites of the telomeric probe were restricted to end chromosome regions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
33
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 14 publications
7
33
0
Order By: Relevance
“…In Schoenus species variation in the number of 45S and 5S rDNA signals was observed but the positions of these sites were conserved. The results agree with the studies on Rhynchospora (Vanzela et al , 2003, Cuscuta approximata (Guerra and Garcia 2004) and Eleocharis (da Silva et al 2005) where the 45S rDNA signal was located terminally. Generally, nucleolar constrictions have been observed in the terminal regions of the holocentric chromosomes of some species in Cyperaceae (Hoshino et al 1993, Vanzela et al 1996, Luceno et al 1998.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In Schoenus species variation in the number of 45S and 5S rDNA signals was observed but the positions of these sites were conserved. The results agree with the studies on Rhynchospora (Vanzela et al , 2003, Cuscuta approximata (Guerra and Garcia 2004) and Eleocharis (da Silva et al 2005) where the 45S rDNA signal was located terminally. Generally, nucleolar constrictions have been observed in the terminal regions of the holocentric chromosomes of some species in Cyperaceae (Hoshino et al 1993, Vanzela et al 1996, Luceno et al 1998.…”
Section: Resultssupporting
confidence: 91%
“…It also appears that the number of signals is fewer in the diploid race than in the polyploidy one. Similar results have been found in the two races of R. tenuis (Vanzela et al 2003). Variation in the size and number of 45S rDNA signals was detected in eight species of Rhynchospora.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…To test the assumption that all holocentromeres are devoid of centromere-specific repeats, we analyzed R. pubera (12,(20)(21)(22). We report here on the first (to our knowledge) conserved centromere-specific repeats of a holocentric species and propose a model of chromosome organization for species with centromeric repeats distributed throughout the entire genome.…”
mentioning
confidence: 99%
“…Theoretically, fusion of holokinetic chromosomes may occur by breaks and reunion at telomeric repeats or at other chromosomal sites. Indeed, Da Silva et al (2005) observed a site of telomeric DNA at the median region of the largest chromosome pair of E. subarticulata (n = 3), whereas in R. tenuis (n = 2) no interstitial site of telomeric DNA was found (Vanzela et al, 2003).…”
Section: Disploidy and Aneuploidy In Plants With Holokinetic Chromosomesmentioning
confidence: 99%